Oral and Maxillofacial Surgery - Schliephake, Henning; Assael, Leon.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Oral & Maxillofacial Surgery founded as Mund-, Kiefer- und Gesichtschirurgie is a peer-reviewed online journal. It is designed for clinicians as well as researchers. The quarterly journal offers comprehensive coverage of new techniques, important developments and innovative ideas in oral and maxillofacial surgery and interdisciplinary aspects of cranial, facial and oral diseases and their management. The journal publishes papers of the highest scientific merit and widest possible scope on work in oral and maxillofacial surgery as well as supporting specialties. Practice-oriented articles help improve the methods used in oral and maxillofacial surgery. Every aspect of oral and maxillofacial surgery is fully covered through a range of invited review articles, clinical and research articles, technical notes, abstracts, and case reports. Specific topics are: aesthetic facial surgery, clinical pathology, computer-assisted surgery, congenital and craniofacial deformities, dentoalveolar surgery, head and neck oncology, implant dentistry, oral medicine, orthognathic surgery, reconstructive surgery, skull base surgery, TMJ and trauma. Time-limited reviewing and electronic processing allow to publish articles as fast as possible. Accepted articles are rapidly accessible online. Clinical studies submitted for publication have to include a declaration that they have been approved by an ethical committee according to the World Medical Association Declaration of Helsinki 1964 (last amendment during the 52nd World Medical Association General Assembly, Edinburgh, Scotland, October 2000). Experimental animal studies have to be carried out according to the principles of laboratory animal care (NIH publication No 86-23, revised 1985).
Keywords: Oral surgery; Maxillofacial surgery; Oral and Maxillofacial Surgery